Plastics piping systems for industrial applications. Polybutene (PB), polyethylene (PE), polyethylene of raised temperature resistance (PE-RT), crosslinked polyethylene (PE-X), polypropylene (PP). Metric series for specifications for components and the system. (26th November 2020) - British Standards Institution,
No abstract available